2020
DOI: 10.1007/s42990-020-00044-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface expressions of morphostructural features at Hasandağ stratovolcano on DEM datasets

Abstract: Although the young pyroclastic cover tends to hide the structural features, derivatives of Digital Elevation Models (DEM) help reveal the morphological elements exposing the structure of the volcanoes. While the shaded relief maps improve the visuality of the DEM data, they are not the best derivatives to express the detailed morphological characteristics of the terrain. Advanced morphometric DEM derivatives, such as Red Relief Image Maps and Openness images, provide improved terrain legibility especially on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Hasandag is an active/subactive volcano having summit fumarole activities [Aydar, 1992, Aydar andGourgaud, 1998]. Diker et al [2018] worked on hydrothermal activities of Hasandag with self-potential, surface temperature and CO 2 measurements and they relate those activities with structural discontinuities [Ulusoy et al, 2021] on the volcano. They concluded that the hydrothermal zone starts above 2250 m; on the summit zone, fumaroles, hot grounds, and water Erkan Aydar et al…”
Section: Discussionmentioning
confidence: 99%
“…Hasandag is an active/subactive volcano having summit fumarole activities [Aydar, 1992, Aydar andGourgaud, 1998]. Diker et al [2018] worked on hydrothermal activities of Hasandag with self-potential, surface temperature and CO 2 measurements and they relate those activities with structural discontinuities [Ulusoy et al, 2021] on the volcano. They concluded that the hydrothermal zone starts above 2250 m; on the summit zone, fumaroles, hot grounds, and water Erkan Aydar et al…”
Section: Discussionmentioning
confidence: 99%
“…8), the vent of the Belbaşhanı Pumice eruption was located near the intersection of the Tuz Gölü fault and the Ulukışla caldera (Fig. 1c; Ulusoy et al 2021;Diker et al 2024). Isomaps indicate that volcanic material was dispersed towards the northeast.…”
Section: Eruption Source Parameter Estimations and Related Uncertaintiesmentioning
confidence: 96%
“…1c) is covered by a debris-avalanche deposit forming a hummocky terrain between the Hasandağ volcano and Ihlara river (Fig. 1c; Kuzucuoğlu et al 2020;Ulusoy et al 2021). Parts of this avalanche deposit are distributed within the Kitreli basin, which lies towards the northeast of Hasandağ and spans the territory between the towns of Yenipınar, Ihlara, and Kitreli (Fig.…”
Section: Geological Setting Of Anatolia and Hasandağ Volcanomentioning
confidence: 99%
See 1 more Smart Citation
“…Moment magnitude of earthquake (M w ), horizontal distance (D) distance between earthquake epicenter and volcanic system. and fumarolic degassing on its western flank with temperatures of up to 68.7 °C and CO 2 levels ∼10,000 ppm are indicative of the presence of an active magmatic system (Dİker et al, 2018;Ulusoy et al, 2020;Aydar et al, 2021). Mid-crustal low-seismic velocity layers beneath the volcanic province may represent magma reservoirs feeding active surface volcanism (Abgarmi et al, 2017).…”
Section: Hasan Dağ Volcanomentioning
confidence: 99%